Active Noise Control Using a Fuzzy Inference System Without Secondary Path Modelling - Sebastian KURCZYK; Marek PAWELCZYK (Archives of Acoustics, 2014)
For many adaptive noise control systems the Filtered-Reference LMS, known as the FXLMS algorithm is used to update parameters of the control filter. Appropriate adjustment of the step size is then important to guarantee convergence of the algorithm, obtain small excess mean square error, and react with required rate to variation of plant properties or noise nonstationarity. There are several recipes presented in the literature, theoretically derived or of heuristic origin.